PERKEMBANGAN HUKUM DAN PENGADILAN PADA ERA ABBASIYAH - Miftakhus Sifa' Bahrul Ulumiyah (Qurthuba: The Journal of History and Islamic Civilization, 2020)
Abstract: This article aims to explore legal justice in the classical Islamic era, specifically in the Abbasid era. This era became an icon of the golden age of Islam—which, of course, law and courts also developed rapidly. However, this era is also a sign that it is in this era that Islamic law is experiencing frigidity. This study uses the historical method with a socio-historical and phenomenological approach. The results of this study note that there were two periods of legal development in the Abbasid era, namely the first Abbasid period and the second Abbasid period. In the first period, law underwent differentiation and the formation of structured legal institutions such as the diwan al-qadhi qudhoh and several judicial bodies. The second period of legal development was more systematic, complete and autonomous, such as the existence of sect autonomy in each region, the formation of new laws, and the order of the judicial system which was so professional and conducive. This research is concluded into three phenomena; Abbasid law, especially in the second period, experienced rapid progress which was conducive to the modern era, the emergence of various schools of thought, government intervention and law enforcement marked by the phenomenon of mihnah, and left traces of the legal frigidity of the later era. Keyword: law, legal justice, Abbasid, development